PERAN UNITED NATIONS CHILDREN’S FUND SEBAGAI CHILD PROTECTION TERHADAP ANAK-ANAK YANG DIREKRUT OLEH KELOMPOK BOKO HARAM PADA KONFLIK BERSENJATA NON INTERNASIONAL DI NIGERIA - Putri Dewi FS; Maria Maya Lestari; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Recruitment of children as part of the armed conflict has enormous impacts, suchas the recruitment of children who are recruited by the Boko Haram group, manychildren are recruited as spies, suicide bombers, cooks, messengers and others. Therecruitment of these children which is the involvement of children in armed conflicts is aviolation of children's rights, so the UN as an international organization gives amandate, namely to UN agencies specifically having one special organ that deals withchildren, namely UNICEF. UNICEF is a place to protect children so that they canremain free and obtain their rights. UNICEF and the UNICEF program will protectchildren from serious violations of their rights. So that the purpose of writing this thesis,namely: First to find out violations of the rights of children who become ChildProtection against the recruitment of children by the Boko Haram group, Second, therole of UNICEF as child protection for children recruited by the Boko Haram group innon armed conflicts in Nigeria, the three obstacles of UNICEF in carrying out its roleas child protection for children recruited by the Boko Haram group in non-internationalarmed conflicts in Nigeria.This type of research can be classified into this type of research, namelynormative legal research, namely a legal research conducted by examining librarymaterials with secondary data. Then, the data that has been collected will be processedand analyzed using descriptive methods by sorting the data so that a conclusion can bedrawnThe results of the research problem there are three main things that can beconcluded. First, there are many violations of children's rights against recruitment byBoko Haram. Both UNICEF as an international organization has an important positionas an IGO, and an international legal subject that has a role as an independent actorand UNICEF is carrying out its role with various efforts to protect children recruited bythe Boko Haram group by asking the Nigerian authorities to sign the Optional ProtocolThe Convention on the Rights of the Child concerning the Involvement of Children inarmed conflicts also prohibits the forced recruitment or conscription of children and thesigning of an action plan to end and prevent the recruitment and use of children. Third,there are several obstacles that occur, namely in terms of funding, access to health andothers.Keywords: Recruitment of Children- The Role of UNICEF- Child Protection